Análisis para la valoración de la arquitectura religiosa presente en la ciudad de Riobamba - Bastidas Auquilla, Diego Fabricio (2022)
Throughout the history of architecture, religious type buildings are the most important line of interest than any other type, since, in most cultures, the universal appeal and splendor of religion made the church the most expressive, enduring and influential building for any community. Allowing to emphasize the cultural richness and providing an important knowledge about a particular historical period, while providing the socio-cultural evolution that has had the society to which it belongs. Understanding the importance that this type of architecture represents and determining that they do not have a fair valuation, with the deep meaning that they keep in their spaces, walls and in the materials used in their construction, “Analysis for the valuation of the religious architecture present in the city of Riobamba” will allow studying the architecture appreciated in different times, to emphasize the values of the works given in a moment, place or in a particular context, thus determining their value independently of the moment in which they were conceived. This research begins with an argumentative interpretation of the state of the art related to the subject, studying religious architecture, which starting with the description of its importance will give way to the historical analysis of the moments that marked the beginnings of this architecture, as well as the events and characteristics that defined it. For the following section that is born from the search of a general vision about the religious architecture present in the city, a study is generated that allows locating and identifying the churches of the city, exposing them in a concise way and in a way that allows us to locate them in a specific order to select and analyze certain works as a next step, oriented its study mainly to the architectural, but as a complement the historical and symbolic, points that in this architecture are presented with a homologous importance; And thus to be able to achieve an own interpretation of the city under architectural parameters.